THE EFFECT OF GOOD CORPORATE GOVERNANCE ON COMPANY VALUE WITH FINANCIAL PERFORMANCE AS A MEDIATING VARIABLE - Eny Widayawati; Ratna Nikin Hardati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
The company aims not only to earn profit but also to increase its value. Firm value is the price that is willing to pay when the company is sold. This study aims to examine the effect of Good Corporate Governance on firm value with financial performance as a mediating variable. This research was conducted at manufacturing companies listed on the IDX for the 2017-2021 period. The sample was determined by purposive sampling and a sample of 60 was obtained. The data analysis technique used was path analysis. The results of the analysis show that management ownership and institutional ownership have no effect on financial performance, independent commissioners have an effect on financial performance, management ownership, independent commissioners, financial performance have an effect on firm value, institutional ownership has no effect on firm value, financial performance has not been able to mediate the relationship between management ownership, independent commissioners on firm value, and financial performance are able to mediate the effect of institutional ownership on firm value.